Dynamic and structural integrity analysis of a complete elevator system through a Mixed Computational-Experimental Finite Element Methodology. (1st April 2018) - Giagopoulos, Dimitrios; Chatziparasidis, Iraklis; Sapidis, Nickolas S.
Highlights: Mixed Computational-Experimental FE Methodology for determining dynamic response. Application and verification of the method on a complete industrial elevator system. Synchronous and non-synchronous activation of the safety gears simulation analysis. Important innovation for the field "analysis and optimization of elevator systems". Abstract: A systematic dynamic and structural integrity analysis of an elevator system, under real dynamic load conditions, is presented in this work. The proposed method constitutes an important innovation for the field "analysis and design optimization of elevator systems". Current elevator design requirements lead to development of lightweight structures which often are of higher complexity. In order to achieve design optimization of these systems, it is important to develop an accurate Finite Element Analysis methodology, to support their precise numerical modeling, also in the worst loading case for their operation. One of the worst loading cases for an elevator system is when the elevator falls free and the safety gear is activated until the elevator stops. Each elevator, when installed in a building, is tested in this loading scenario. This means, that should be designed to withstand in these loads and not to have any damage after this test. One of the special features of this paper is that the study was performed on a complete industrial elevator system, including all details/complexities of a commercial system. Comparison of the numerical and experimental data verifies that the proposed "mixed computational-experimental" analysis method is quite reliable, concluding application/verification of the method on a complete industrial elevator system.